Development and Implementation of a Machine to Increase the Production and the Quality of a Compost - Camila Mori de Oliveira; Andrea Sammito; Mauro Boano; Matteo Fischetti; Lorenzo Toso; Roberta Pizio; Rossana Bellopede; Paola Marini (Recycling)
The composting sector plays a crucial role in the urban waste management system and is essential for advancing towards a circular economy. All organic matter can be entirely recovered from waste collection, except for the extraneous fractions present as impurities. In the studied waste composting plant, three fractions are produced: >50 mm (waste not idoneous for compost), <12 mm (suitable for compost market) and 50–12 mm (overflow). The latter is used as inoculum and therefore recirculates many times, reducing the sizes of its constituents, which are mainly plastic films falling into the lower class <12 mm, where they are concentrated. The goal of this study is to reduce the quantity of undesirable materials present in the 50–12 mm class in order to increase the quality of the compost produced. For this reason, a compost characterization was carried out and a plant solution was proposed: the inclusion of a mesh conveyor belt, with beater rollers and an aspiration system at the end. The fine organic material passes through the mesh sieve, and it is moved apart from the overflow material, in which the light plastics are aspirated. More than 10% of the overflow weight is recovered as clean compost, with very low percentages of undesired remaining. A reduction in plastic impurity of 75% is reached.